Spectrophotometric Determination of Chlorpropamide in Bulk and Dosage Form by Complexation with Chloranilic Acid - Mbah, C. J.; Okorie, N. H. (Journal of Scientific Research, 2010)
A spectrophotometric study of chlorpropamide is described. The method is based on the charge-transfer complexation between chlorpropamide (the n-electron donor) with chloranilic acid (the p-acceptor) to form a violet coloured complex having absorption maxima at 530 nm. Beer’s law is obeyed for up to 5-25 mg/ml of chlorpropamide. Results of the analysis of this method were validated statistically by recovery studies. The proposed method is simple, accurate and precise for the quantitative determination of chlorpropamide in bulk and tablet formulations. Keywords: Chlorpropamide; Spectrophotometry; Chloranilic acid. © 2011 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi:10.3329/jsr.v3i1.4808 J. Sci. Res. 3 (1), 207-212 (2011)